2020
DOI: 10.1186/s12864-020-06998-w
|View full text |Cite
|
Sign up to set email alerts
|

Circular DNA intermediates in the generation of large human segmental duplications

Abstract: Background: Duplications of large genomic segments provide genetic diversity in genome evolution. Despite their importance, how these duplications are generated remains uncertain, particularly for distant duplicated genomic segments. Results: Here we provide evidence of the participation of circular DNA intermediates in the single generation of some large human segmental duplications. A specific reversion of sequence order from A-B/C-D to B-A/D-C between duplicated segments and the presence of only microhomolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Taken together, the structure observed is consistent with a duplication mechanism involving circular intermediates as recently established by Chicote et al (2020) . In the case described here recombination between two SVA elements mediates reintegration of the circular intermediate into the genome ( fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Taken together, the structure observed is consistent with a duplication mechanism involving circular intermediates as recently established by Chicote et al (2020) . In the case described here recombination between two SVA elements mediates reintegration of the circular intermediate into the genome ( fig.…”
Section: Resultssupporting
confidence: 88%
“…Recently, SDs were found to be significantly overrepresented in sperm eccDNA ( Mouakkad-Montoya et al 2021 ). To date, only a relatively small number of duplication events generated by this mechanism has been characterized ( Chicote et al 2020 ; Takahashi and Innan 2020 ). Fundamental questions regarding circularization and integration are still unanswered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fate of SD-bearing nscDNA (formation, reintegration, and degradation) in germ cells could be associated with genetic variations since SDs are subject to meiosis-specific DNA double-strand breaks ( 55 ), which would facilitate the integration of nscDNA into chromosomes. A trace of this mechanism can be found within SD clusters of the human genome ( 56 58 ). In yeast ( 59 ) and bovine ( 60 ), circular intermediates have been implicated in chromosomal amplifications or genic translocation events.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings show that elevated transcription increases the chance of a gene duplication mutation (Hull et al, 2017;Wilson et al, 2015;Thomas and Rothstein, 1989;Aguilera and Gaillard, 2014;Hamperl et al, 2017), likely by local destabilization of the genome (Aguilera, 2002;Gómez-González and Aguilera, 2019) followed by downstream mechanisms involving RNA (Kaessmann et al, 2009) or DNA intermediates (Chicote et al, 2020;Durkin et al, 2012;Takahashi and Innan, 2020). A direct connection between transcription and gene duplication mutation rates was exemplified in yeast, where copy number amplification of the CUP1 gene results in adaptation to high copper concentration: by replacing the CUP1 promoter sequence with a galactose-inducible promoter, Hull et al (2017) have shown that CUP1 transcription induces gene copy number amplification under galactose stimulation and in the absence of copper selection, suggesting that copy number amplification of the wild-type CUP1 can be caused mechanistically by transcription.…”
Section: Gene Duplication As Mutational Replacementmentioning
confidence: 99%